Postural deformities of the spine and lower exremities in school children: an epidemiologic study - Nafiz Akman, M.; Ersoy, Yuksel; Ari, Murat; Sari, Zubeyir; Sari, Aysen; Tanacan, Sevim (Annals of Medical Research, 2021)
None
Keywords: s : Posture, scoliosis, kyphosis, pes planus